x+9=18+-2x is a simple algebraic equation that can be solved to find the value of ‘x’. Let’s break down the equation and go through the steps to solve it.

First, let’s simplify the equation by combining like terms:

x + 9 = 18 – 2x

To solve for ‘x’, we need to isolate the variable on one side of the equation. We can achieve this by performing inverse operations. Let’s start by getting rid of the -2x on the right side by adding 2x to both sides:

x + 2x + 9 = 18 – 2x + 2x

This simplifies to:

3x + 9 = 18

Next, we want to isolate the term with ‘x’, so let’s subtract 9 from both sides:

3x + 9 – 9 = 18 – 9

This simplifies to:

3x = 9

To solve for ‘x’, we divide both sides of the equation by 3:

(3x)/3 = 9/3

The 3’s cancel out on the left side, leaving us with:

x = 3

So, the value of ‘x’ in the equation x+9=18+-2x is 3.

To further illustrate the solution, let’s plug the value of ‘x’ back into the original equation and verify if it holds true:

3 + 9 = 18 + (-2 * 3)

This simplifies to:

12 = 18 – 6

12 = 12

As we can see, both sides of the equation are equal, which confirms that our solution, x = 3, is correct.

To summarize:

  • The given equation x+9=18+-2x can be solved using algebraic techniques.
  • By simplifying and isolating the variable ‘x’, we found that x = 3.
  • Plugging the value of ‘x’ back into the original equation, we verified that the solution is correct.

I hope this explanation helped! If you have any further questions, feel free to ask.

Leave a Comment